Comparative analysis of three BMI cutoffs for five metabolic abnormalities in the population of Western Guangdong, China - Pang, Dengwen; Chen, Meizhu; Xiao, Chengwen; Zhuang, Ruijian; Kong, Chengyu; Xiao, Mengyuan (Frontiers in Nutrition, 2025)
Background and objectiveObesity is a core risk factor for metabolic diseases, and body mass index (BMI) serves as a key tool for assessing obesity. Current internationally adopted BMI standards (such as the WHO universal standard and the Asia-Pacific standard) differ from the Chinese standard developed based on data from the Chinese population. Given the unique genetic background and lifestyle of the population in Western Guangdong, China, their spectrum of metabolic diseases may exhibit distinct characteristics. This study aims to systematically compare the predictive capabilities of the three commonly used BMI standards for the “five highs” (hypertension, dyslipidemia, diabetes, hyperuricemia, and hyperhomocysteinemia) and their clustering risk in this population, providing evidence for localized precision prevention and control.MethodsThis cross-sectional study included 5,667 permanent residents in Western Guangdong who completed health examinations between 2023 and 2024. Participants were grouped according to three BMI standards: Chinese (overweight ≥24 kg/m2, obese ≥28 kg/m2); WHO General (overweight ≥25 kg/m2, obese ≥30 kg/m2); WHO Asia-Pacific (overweight ≥23 kg/m2, obese ≥25 kg/m2). Multivariate logistic regression and restricted cubic spline (RCS) analyses examined the association between BMI and the risk of “five highs” (hyperglycemia, hyperlipidemia, hypertension, hyperuricemia and hyperhomocysteinemia) and their clustering. Subgroup analyses by age and sex were conducted.ResultsIndividuals classified as overweight or obese according to Chinese criteria showed the strongest risk gradient for clustering two or more metabolic risks, with overweight and obesity increasing the risk of the five high by 79 and 140%, respectively. RCS analysis revealed a nonlinear positive correlation between BMI and the risk of clustering the “five highs,” with the most significant change in risk slope occurring near the cut-off points defined by the Chinese standard (24 and 28 kg/m2). Subgroup analysis further indicated that males and younger individuals exhibited heightened sensitivity to metabolic risks associated with increasing BMI.ConclusionAmong the population in Western Guangdong, China, the Chinese BMI standard outperformed both the WHO universal and Asia-Pacific standards in identifying “five highs” and their clustered risks, demonstrating greater sensitivity in screening high-risk individuals. It is recommended as the preferred tool for primary prevention of metabolic diseases and public health strategy development in this region.